Juridical Problems of Ministers' Administrative Authority in the Determination of Domain Name Registrars in Indonesia - Andi Budimansyah; Akmal Syaddad; Frida Junariah; Indri Lestari; Siti Fajri Ilaika (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2026)
Domain name governance is no longer solely a technical issue of internet addressing, but has become part of the legal infrastructure of digital identity, cybersecurity, consumer protection, and digital sovereignty of the state. In Indonesia, Government Regulation Number 71 of 2019 concerning the Implementation of Electronic Systems and Transactions normatively recognizes Registry and Registrar as domain name managers. However, in practice, formal designation by the Minister seems to be given to the Indonesian Internet Domain Name Manager as the